2023
DOI: 10.3390/healthcare11060849
|View full text |Cite
|
Sign up to set email alerts
|

A Scoping Review with Bibliometric Analysis of Para-Rowing: State of the Art and Future Directions

Abstract: Para-rowing is a format of rowing practiced by people with different types of disabilities, thanks to adapted equipment set-ups and regulations. Para-rowing made its debut recently at the 2008 Paralympic Games. According to the mandate of the “International Paralympic Committee”, para-rowers should be enabled to pursue sporting excellence. Therefore, rigorous research is needed in terms of well-designed, high-quality studies. To the best of our knowledge, there are no systematic appraisals of the body of schol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 49 publications
0
2
0
Order By: Relevance
“…and L.P.). Citations were exported and dealt with by means of the "Research Information Systems" (RIS) file format [40,41]. Duplicate items were removed using open-source citation management software (Zotero version 6.0.30 for Windows, Corporation for Digital Scholarship).…”
Section: Relevant Studies Identificationmentioning
confidence: 99%
See 1 more Smart Citation
“…and L.P.). Citations were exported and dealt with by means of the "Research Information Systems" (RIS) file format [40,41]. Duplicate items were removed using open-source citation management software (Zotero version 6.0.30 for Windows, Corporation for Digital Scholarship).…”
Section: Relevant Studies Identificationmentioning
confidence: 99%
“…VOSviewer version 1.6.18, Gephi version 0.10.1, and Cytoscape version 3.9.1 were utilised for bibliometric data extraction, processing, and graph/network visualisation [40,41]. These graphs/networks were, subsequently, investigated from a quantitative perspective, by calculating an array of various indicators, namely, (i) the count of scholars (authors and coauthors in the bibliographic graph/network); (ii) the number of countries represented in the network; (iii) the number of publications per author or research organisation, both in terms of absolute figures and as a percentage of the total; (iv) the quantity of separate connected components, serving as an indicator of network connectivity; (v) the mean number of adjacent nodes for each node in the network; (vi) the total count of links connecting nodes in the network; (vii) the overall strength of connections between nodes, also known as the total edge weight; (viii) the length of various paths within the network, including the shortest paths (i.e., distance) and the average shortest path length (i.e., characteristic path length), along with other related parameters; (ix) the network's diameter (the longest shortest path) and radius (the shortest longest path); (x) the density of the network, indicating how connected it is; (xi) the variation in connectivity across the network, often referred to as network heterogeneity; (xii) the extent to which a network is centralised around certain nodes; (xiii) the number of scholar clusters, also known as scholarly communities, within the network; (xiv) the count of research organisation or institution clusters or communities within the network; and (xv) the clustering coefficient, which measures the level of connectivity among a node's neighbours in the network.…”
Section: Bibliometrics Analysismentioning
confidence: 99%
“…The academic community of para-rowing was found to consist of 78 researchers, 16 (20.51%) of whom were highly interconnected. The study identified gaps in areas such as sports nutrition, doping, and psychological aspects among para-rowers who are not visually impaired [26]. The same Italian group evaluated paralympic powerlifting (PP) through a scoping literature review enhanced by a bibliometric analysis using large databases.…”
mentioning
confidence: 99%